Pengaruh Person Organization Fit, Organizational Citizenship Behavior, Dan Burnout Terhadap Kinerja Karyawan Bank Bri Kanca Manna Bengkulu Selatan - savella, fran; Puspita, Veny; Fauzan, Fauza (JMB : Jurnal Manajemen dan Bisnis, 2024)
The purpose of this research is to find out how much influence person organization fit, organizational citizenship behavior and burnout have on the employees performance of Bank BRI Kanca Manna South Bengkulu . The variables of this research are person organization fit, organizational citizenship behavior and burnout. The research method used is an explanatory research approach. This research uses quantitative data. Data comes from distributing questionnaires employees to Bank BRI Kanca Manna south Bengkulu. The research population was all employees of Bank BRI Kanca Manna South Bengkulu, totaling 45 employees, using a saturated sampling technique. The analytical tool used in this research uses SPSS 22. The data analysis method used is multiple linear regression, t test and f test. The results of this research are; (1) Person Organization Fit (X1) has a partial and positive effect on employee performance (Y) Bank Bri Kanca Manna South Bengkulu (2) Organizational Citizenship Behavior (X2) has a partial and positive effect on employee performance (Y) Bank Bri Kanca Manna South Bengkulu (3) Burnout (X3) has a partial and positive effect on employee performance (Y) Bank Bri Kanca Manna South Bengkulu (4) Person Organization Fit (X1), Organizational Citizenship Behavior (X2) and Burnout (X3) on employee performance (Y) together has a simultaneous influence.